Predictive Value of Excision Repair Cross Complementation Group 1 (ERCC1) by Immunohistochemistry for Determining Neoadjuvant Chemotherapy Response in Triple-Negative Breast Cancers - Atif Ali Hashmi; Yumna Ajaz; Muhsana Sajjad; Fazail Zia; Muhammad Irfan; Syed Muhammad Abu Bakar; Erum Yousuf Khan; Naveen Faridi (The Breast Journal)
Conclusion: In this study, we established the role of negative ERCC1 expression in predicting the response to chemotherapy in neoadjuvant TNBC. Therefore, ERCC1 can be used as a predictive marker to stratify patients who will benefit from neoadjuvant therapy. Moreover, we also noted an association between ERCC1 expression and nodal metastasis; however, more large-scale studies are needed to establish its role as a prognostic biomarker in TNBC.